Maternal Chronodisruption Throughout Pregnancy Impairs Glucose Homeostasis and Adipose Tissue Physiology in the Male Rat Offspring - Halabi, Diego; Richter, Hans G.; Mendez, Natalia; Kähne, Thilo; Spichiger, Carlos; Salazar, Esteban; Torres, Fabiola; Vergara, Karina; Seron-Ferre, Maria; Torres-Farfan, Claudia (Frontiers in Endocrinology, 2021)
Compelling evidence in rats support that gestational chronodisruption induces major changes in maternal circadian rhythms, fetal development and that these changes impact adult life at many physiological levels. Using a model of chronic photoperiod shifting throughout gestation (CPS); in which pregnant female rats (Sprague Dawley strain; n = 16 per group) were exposed to lighting schedule manipulation every 3–4 days reversing the photoperiod completely or light/dark photoperiod (12/12; LD), we explored in the adult rat male offspring; body weight gain, glucose homeostasis, adipose tissue content, adipose tissue response to norepinephrine (NE) and adipose tissue proteomic in the basal condition with standard diet (SD) and in response to high fat diet (HFD). In adult CPS male (100-200 days-old; n = 8 per group), we found, increasing body weight and adiposity, under SD. Also, we found an increased response to intraperitoneal glucose (IGTT). After 12 weeks of HFD, white adipose tissue depots in CPS offspring were increased further, and higher IGTT and lower intraperitoneal insulin tolerance response were found, despite lack of changes in food intake. In in vitro experiments, we observed that adipose tissue (WAT and BAT) glycerol response to norepinephrine from CPS offspring was decreased, and it was completely abolished by HFD. At proteomic level, in CPS adipose tissue, 275 proteins displayed differential expression, compared with LD animals fed with a standard diet. Interestingly, CPS offspring and LD fed with HFD showed 20 proteins in common (2 upregulated 18 downregulated). Based on these common proteins, the IPA analysis found that 2 functional pathways were significantly altered by CPS: the network 1 (AKT/ERK) and the network 2 (TNF/IL4; Data are available via ProteomeXchange with identifier PXD026315). The present data shows that gestational chronodisruption induced deleterious effects in adipose tissue recruitment and function; supporting that adipose tissue function was programmed in utero by gestational chronodisruption, inducing deficient metabolic responses that persist into adulthood.